2019
DOI: 10.1021/acsenergylett.9b01427
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electron–Phonon Coupling in the Thermal Evolution of Bulk Rashba-Like Spin-Split Lead Halide Perovskites Exhibiting Dual-Band Photoluminescence

Abstract: The optoelectronic properties of lead halide perovskites strongly depend on their underlying crystal symmetries and dynamics, sometimes exhibiting a dual photoluminescence (PL) emission via Rashba-like effects. Here we exploit spin-and temperature-dependent PL to study single crystal APbBr3 (A= Cs and methylammonium; CH3NH3) to evaluate peak energy, intensity and linewidth evolutions of the dual emissions. Both materials are identified to have two temperature regimesabove and below approximately 100 Kbeing gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 61 publications
6
90
0
1
Order By: Relevance
“…Significant discrepancies are found in literature about the position of the PL peak with values between 500 and 574 nm, and dual PL emission has also been observed . The variation in PL position and the dual PL emission have been attributed to different origins such as reabsorption, reabsorption combined with carrier diffusion, distinct emission from bulk and surface states (due to different bandgaps or different perovskite phases), different band energies of ordered and disordered domains, and finally to a Rashba‐like spin‐split . These phenomena are discussed below in more detail.…”
Section: Photoluminescence Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Significant discrepancies are found in literature about the position of the PL peak with values between 500 and 574 nm, and dual PL emission has also been observed . The variation in PL position and the dual PL emission have been attributed to different origins such as reabsorption, reabsorption combined with carrier diffusion, distinct emission from bulk and surface states (due to different bandgaps or different perovskite phases), different band energies of ordered and disordered domains, and finally to a Rashba‐like spin‐split . These phenomena are discussed below in more detail.…”
Section: Photoluminescence Propertiesmentioning
confidence: 98%
“…Finally, an additional electronic phenomenon that can contribute to the dual emission observed in MAPbBr 3 is the strong Rashba-like spin-split present in this perovskite. [91,[99][100][101] The combination of two phenomena leads to this effect: First, the strong SOC that is induced by the heavy Pb atom and second, a static or dynamic breaking of the inversion symmetry in the crystal that leads to the appearance of an effective magnetic field on the electrons by SOC, lifting spin degeneracy and splitting the band electronic structure. [91] How the Rashba-like effect leads to dual emission is explained by Steele et al, [91] supported by temperature dependent PL measurements, and is schematically shown in Figure 3f.…”
Section: Further Processes Affecting the Pl Peak Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49–53 ] However, this emission feature can be also correlated to the Rashba effect induced by the centrosymmetry breaking by the perovskite's organic cations. [ 54,55 ] In addition, the grain size of conventional CH 3 NH 3 PbBr 3 bulk crystals can also determine which band structure dominates the overall PL spectra in between different structural phases (e.g., tetragonal‐to‐orthorhombic phase transition) at low temperature (e.g., 40–50 K), generating a dual‐color emission when the same weight in both bands is achieved upon an optimum grain size of about 100 nm. [ 56 ] Recently, Wu et al clarified that dual‐color emission is even a common character of all lead halide perovskites, but the relative intensity of the low‐energy peak (i.e., at longer wavelength) strongly depends on the surrounding conditions, such as the environmental temperature, and can lead to a nondistinguishable second peak in some cases.…”
Section: Direct–indirect Transitions Induced Dual‐color Emissionmentioning
confidence: 99%
“…12,13 By suppressing nonradiative recombination and balancing carrier injection, the luminescence efficiency of perovskite-based devices has been significantly improved. [14][15][16][17] Despite a significant increase in efficiency, the development of 3D-perovskite-based LEDs is plagued by their poor stability. 18,19 Firstly, because of their soft structure, they can easily decompose at high-temperature or high-humidity.…”
Section: Introductionmentioning
confidence: 99%